(untitled) (Journal of Contemporary Issues in Accounting, 2024)
This study investigated the effect of Federal Government’s capital expenditures profiling on the economic health of Nigeria between 1981 and 2023. The multiple regression method of analysis was applied to estimate the parameters. The study also disaggregated the expenditure of the government into administration, social and community services, economic services and transfers, while the health of the economy was measured by the nominal value of gross domestic product (GDP) The data for the study were obtained from the Central Bank of Nigeria Statistical Bulletin, 2022 and 2023. From the findings of this study, government expenditure on administration, social and community services and transfers were found to be positive and statistically significant with economic growth of Nigeria, whereas, government expenditure on economic services has negative and insignificant effect on economic growth. Based on the findings, the study recommends that government should increase budget allocations to these sectors and ensure that the funds are properly monitored so as to feel the effect of these funds on the growth of the economy.